REFLEKSI KEGIATAN SIMULASI MENGAJAR MATERI LAMBANG - LAMBANG PANCASILA DALAM MENANAMKAN NILAI-NILAI PANCASILA DI KELAS - Khairunisa, Alvina; Putri, Salsabilla Cahaya; Situmorang, Joya Amelia Patricia; Manurung, Berliana Afriani; Panggabean, Xena Bintang (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to reflect on teaching simulation activities that have been carried out by students which focus on material regarding the symbols of Pancasila and the values contained in Pancasila as well as how to instill these Pancasila values in the classroom. Pancasila consists of five precepts and has a symbol, each of which represents the core values of Pancasila. Teaching simulation activities are carried out to increase students' understanding as prospective teachers and their role as students regarding Pancasila values. This research was conducted to find out the results of teaching simulations by reflecting on these activities to find out what lessons and teaching were learned, as well as what activities were successful and what needs to be improved, as well as what kind of experiences will influence the way I teach in the future. With this research, it is hoped that prospective teachers can improve their ability to teach according to students' learning styles so that learning activities can achieve the desired goals. Keywords: Simulation, Citizenship, Emblem, Pancasila, Educator.